The impact of oocyte central granularity on ICSI practice: developmental competence of dysmorphic and morphologically normal companion oocytes - Buratini, Jose [UNESP]; Moutier, Clarissa; Guglielmo, Maria Cristina; Turchi, Diana; Webb, Robert; De Ponti, Elena; Renzini, Mario Mignini; Canto, Mariabeatrice Dal (Springer Nature, 2023)
Purpose: To assess the effects of oocyte central granularity and its underlying endocrine environment on developmental competence of dysmorphic and morphologically normal oocytes. Methods: Retrospective cohort study including 1,082 patients undergoing autologous ICSI cycles. Of these, 211 patients provided 602 oocytes with central granularity (CG) and 427 morphologically normal cycle companion oocytes (NCG). The remaining 871 patients provided only morphologically normal oocytes in cycles not yielding dysmorphic oocytes (N). Patient profile associated with CG was characterized, and fertilization rates, early morphokinetics and live birth rates were compared between N, CG and NCG groups. Patient characteristics associated with implantation and delivery performance of CG-derived embryos were assessed. Results: CG was associated with higher maternal age, basal FSH concentrations and total FSH dose, but with lower circulating AMH (p ≤ 0.035). Fertilization rates were reduced and early morphokinetic parameters were delayed in CG (p < 0.025) and NCG (p < 0.05) groups as compared to the N group. Embryos derived from CG oocytes achieved a markedly lower live birth rate (14.9%) as compared to those derived from NCG (36.8%; p = 0.03) and N oocytes (29.8%; p = 0.002). The negative relationship between CG and live birth was confirmed by a multivariate analysis controlling for potential confounders (OR:2.59, IC:1.27–5.31; P = 0.009). Implantation and delivery rates following transfers of CG-derived embryos were inversely associated with maternal age. Conclusion: CG oocytes, but not their morphologically normal cycle companions, have severely compromised developmental competence. Maternal age should be a key parameter in deciding whether or not to utilize CG oocytes in ICSI cycles.
Keywords: Fertilization; Live birth; Maternal age; Morphokinetics; Oocyte central granularity